Intensive insulin therapy, insulin sensitisers and insulin secretagogues for burns: A systematic review of effectiveness and safety. Issue 6 (September 2018) - Campbell, Jared M.; Adanichkin, Natalia; Kurmis, Rochelle; Munn, Zachary
Highlights: IIT reduces mortality in pediatric burn patients compared to loose glycemic control. IIT does not affect mortality in adult burn patients compared to moderate glycemic control. Insulin sensitizers and secretagogues may be useful as adjuvants. Abstract: This systematic review investigated the effectiveness and safety of intensive insulin therapy (IIT), insulin secretagogues and sensitisers in burn patients. PubMed, Embase, clinicaltrials.gov and Cochrane central were searched from 1990 to 2016. Title/abstract screening, full-text review, critical appraisal and data extraction were carried out by two independent reviewers. Inclusion criteria were hospitalised burn patients, IIT, insulin sensitisers or secretagogues and the outcomes mortality, length of stay, resting energy expenditure, blood glucose, catabolism, or complications. We identified 594 potential studies of which 13 were included. Five studies investigated IIT in paediatric patients, 3 investigated IIT in adults and 5 investigated sensitisers or secretagogues. Glycaemic targets differed with age group — paediatric studies compared IIT to loose glycaemic control while adult studies compared IIT to more moderate control. Meta-analyses were limited by differences in outcome reporting, however mortality was increased in children by loose glycaemic control (OR = 3.78, 95%CI 1.19–12.02) but not significantly affected in adults by moderate compared to tight control. Meta-analyses could not be performed for sensitisers or secretagogues. These findings support recommendations that moderate insulin administration (130–150 mg/dL) is the prudent approach in burn patients. The evidence is relatively sparse and further research is warranted.